Effects of various degrees of esterification on antioxidant and immunostimulatory activities of okra pectic-polysaccharides - Li, Wei; Li, Jie; Wang, Jin; He, Yuan; Hu, Yi-Chen; Wu, Ding-Tao; Zou, Liang (Frontiers in Nutrition, 2022)
Pectic-polysaccharides are considered as one of the most abundant bioactive components in okra, which possess various promising health-promoting effects. However, the knowledge regarding the structure-bioactivity relationship of okra pectic-polysaccharides is still limited. In this study, effects of various degrees of esterification (DEs) on in vitro antioxidant and immunostimulatory activities of okra pectic-polysaccharides were analyzed. Results displayed that okra pectic-polysaccharides with high (42.13%), middle (25.88%), and low (4.77%) DE values were successfully prepared by mild alkaline de-esterification, and their primary chemical structures (compositional monosaccharide and glycosidic linkage) and molecular characteristics (molecular weight distribution, particle size, and rheological property) were overall stable. Additionally, results showed that the notable decrease of DE value did not significantly affect antioxidant activities (ABTS and nitric oxide radical scavenging abilities as well as ferric reducing antioxidant power) of okra pectic-polysaccharides, suggesting that the DE was not closely related to its antioxidant activity. In fact, the slight decrease of antioxidant activity of okra pectic-polysaccharides after the alkaline de-esterification might be attributed to the slight decrease of uronic acid content. Nevertheless, the immunostimulatory effect of okra pectic-polysaccharides was closely related to its DE, and a suitable degree of acetylation was beneficial to its in vitro immunostimulatory effect. Besides, the complete de-acetylation resulted in a remarkable reduction of immune response. The findings are beneficial to better understanding the effect of DE value on antioxidant and immunomodulatory activities of okra pectic-polysaccharides, which also provide theoretical foundations for developing okra pectic-polysaccharides as functional foods or health products.